2021
DOI: 10.31224/osf.io/s7zm4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Covid-19 Pandemic in Construction Labor Productivity: A Quantitative and Qualitative Data Analysis

Abstract: This research aims to identify and analyze the various factors affecting construction labor productivity covering the period from December 9, 2020 - January 31, 2021, a year after it was declared Covid-19 a pandemic. Due to the pandemic effect, the local government units in four selected study areas imposed intermittent Enhance Community Quarantine on all places to control the Coronavirus spread in compliance with the health department protocol. Fifty-five questionnaires returned out of 63 distributed are tabu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Value can range from -1 to +1. Table 6 indicates the summarized correlation results [9]. It shows the summarized Spearman correlation coefficient suggested that there is a strong correlation between all groups of factors.…”
Section: Correlation On Significant Factors Affecting Supervision Practicementioning
confidence: 96%
See 1 more Smart Citation
“…Value can range from -1 to +1. Table 6 indicates the summarized correlation results [9]. It shows the summarized Spearman correlation coefficient suggested that there is a strong correlation between all groups of factors.…”
Section: Correlation On Significant Factors Affecting Supervision Practicementioning
confidence: 96%
“…An effective supervisor dealt with several skills, including management, human and leadership skills, motivation, communication, and organizational behavior [8]. Supervision has been a less significant effect on the construction project implementation during the COVID-19 pandemic as per the respondents, according to [9]. These abilities can be improved through formal training.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement system was created to measure a specific concept by asking a group of people a series of questions (items). Internal consistency is defined as the extent to which all questions positively contribute to measuring the same concept or construct [12,13,14]. Besides, internal consistency is expressed as the proportion of the test variance attributable to a group of items, which measures the reliability coefficient alpha [13].…”
Section: Reliability Testmentioning
confidence: 99%
“…Where: = Number of Items 2 = variant items 2 = total score variant A high value of the Cronbach's alpha implies a higher internal consistency of the construct 2 . The higher the coefficient, the stronger the linear relationship of the items is correlated and the higher the internal consistency cited by [13,14].…”
Section: Reliability Testmentioning
confidence: 99%
See 1 more Smart Citation